ANALISIS DAYA SAING SEKTOR PARIWISATA DALAM MENINGKATKAN PERTUMBUHAN EKONOMI DAERAH DI KOTA PARIAMAN - Syofria Meidona; Fakhrur Rozi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Tourism sector is one of strategic sector’s in enhancing local revenue. Revenue from tourism activities have contributed in employment, promote employment in these sub-sectors of tourism. In this study the tourism object to be studied is pariaman regency which is one of the areas that have the potential for high value tourism. In this research measuring the competitiveness of the tourism industry can use variables competitiveness using four indicators used World tourism organization (WTO), namely, Human Tourism Indicator (HTI), Infrastructure Development Indicator (IDI), Environtment Indicator (EI), openess Indicator (OI)). This study uses secondary data. The analytical method used in this study is the tourism competitiveness index. The analysis showed that the tourism competitiveness in the eighth indicator variable IDI (Infrastructure Development Indicator) Environtment Indicator (EI), shows the value high competitiveness, while other indicators have of low competitiveness.